Make A Film - Pipe, Jim (London Franklin Watts, 2012)
Have you got the talent to make a film? Find out what it takes to make a film with this book. Packed with hints, skills and tips to get you noticed, this book will help you to focus all of that creative energy!
Include Color Illustrations
Keywords: Cinematography